Tanggung Jawab Hukum Notaris dan Pengurus Perusahaan Atas Pembuatan Akta Korporasi - Alfath, Safira Rasheesa (JURNAL PENELITIAN SERAMBI HUKUM, 2026)
This study examines the responsibilities of notaries and corporate organs in the preparation of corporate deeds. Currently, practices still exist in which notaries are insufficiently thorough in verifying the authority of corporate organs, while corporate organs sometimes do not fully understand the limits of their authority, creating the risk of legally defective deeds. Ideally, notaries should ensure that all shareholders’ meeting approvals and corporate organ authorities comply with legal provisions, particularly those stipulated in the Limited Liability Company Law (UU Perseroan Terbatas), as well as relevant court decisions. The main research question is how the responsibilities of notaries and corporate organs in drafting corporate deeds can be carried out in a legally valid and secure manner. This study employs a normative juridical method with a case study approach based on court decisions related to violations of Article 102 of the Limited Liability Company Law and legal literature analysis. The results indicate that notarial negligence in verifying documents or errors by corporate organs in exercising their authority can pose serious legal risks to the company and third parties. The study emphasizes the need for more systematic verification procedures by notaries, a deeper understanding by corporate organs regarding corporate authority, and stricter legal oversight to minimize legal risks and strengthen corporate governance.